Wnt addiction of genetically defined cancers reversed by PORCN inhibition - Madan, B (Oncogene, 2016)
Enhanced sensitivity to Wnts is an emerging hallmark of a subset of cancers, defined in part by mutations regulating the abundance of their receptors. Whether these mutations identify a clinical opportunity is an important question. Inhibition of Wnt secretion by blocking an essential post-translational modification, palmitoleation, provides a useful therapeutic intervention. We developed a novel potent, orally available PORCN inhibitor, ETC-1922159 (henceforth called ETC-159) that blocks the secretion and activity of all Wnts. ETC-159 is remarkably effective in treating RSPO-translocation bearing colorectal cancer (CRC) patient-derived xenografts. This is the first example of effective targeted therapy for this subset of CRC. Consistent with a central role of Wnt signaling in regulation of gene expression, inhibition of PORCN in RSPO3-translocated cancers causes a marked remodeling of the transcriptome, with loss of cell cycle, stem cell and proliferation genes, and an increase in differentiation markers. Inhibition of Wnt signaling by PORCN inhibition holds promise as differentiation therapy in genetically defined human cancers.